1986
DOI: 10.1002/j.1460-2075.1986.tb04285.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for light-induced 13-cis , 14-s-cis isomerization in bacteriorhodopsin obtained by FTIR difference spectroscopy using isotopically labelled retinals

Abstract: We have obtained by Fourier transformed infra‐red (FTIR)‐spectroscopy BR‐K, BR‐L and BR‐M difference spectra of bacteriorhodopsin regenerated with isotopically labelled retinals. Thereby, we are able to assign reliably the C14–C15 and C=N stretching vibrations of the various intermediates. The lower C14–C15 stretching vibration frequency in L as compared with 13‐cis protonated Schiff base model compounds indicates a 13‐cis, 14‐s‐cis configuration of the retinal in this species. The unusually low C=N stretching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
157
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 186 publications
(170 citation statements)
references
References 25 publications
11
157
0
1
Order By: Relevance
“…In a recent study, Smith et al (8) examined the conformation of the C14-C15 bond in K and L550 by recognizing that one characteristic of an s-cis bond is the -100 cm -1 lowering of the C14-C15 stretching mode. The C14-C15 mode in L550 was assigned at ==1172 cm-1, close to the 1155 cm-1 value observed in later Fourier transform infrared studies (9). The absence of any large frequency-lowering of this mode compared with the 13-cis protonated Schiff base (PSB) suggested that the chromophore was 14-s-trans.…”
supporting
confidence: 76%
“…In a recent study, Smith et al (8) examined the conformation of the C14-C15 bond in K and L550 by recognizing that one characteristic of an s-cis bond is the -100 cm -1 lowering of the C14-C15 stretching mode. The C14-C15 mode in L550 was assigned at ==1172 cm-1, close to the 1155 cm-1 value observed in later Fourier transform infrared studies (9). The absence of any large frequency-lowering of this mode compared with the 13-cis protonated Schiff base (PSB) suggested that the chromophore was 14-s-trans.…”
supporting
confidence: 76%
“…39 The IR intensity of the C-C stretching vibrations of the retinal is negligible unless the SB is protonated. 23,58 The absence of positive bands in this region (beside one weak band at 1176 cm −1 ) confirms that an intermediate with deprotonated SB is predominantly accumulated. A detailed analysis of the retinal bands has recently been published.…”
Section: A Characterization Of Spectral Changes In Cachr1 Under Contmentioning
confidence: 66%
“…The first recorded spectrum (6.5 ms after the laser pulse) lacks positive bands in the C-C stretching region of the retinal (1100-1300 cm −1 ), a characteristic feature for intermediates with deprotonated SB. 23,58 Thus, the spectrum recorded at 6.5 ms after pulsed excitation represents an almost pure P 2 380 spectrum ( Fig. 2(b), top).…”
Section: A Characterization Of Spectral Changes In Cachr1 Under Contmentioning
confidence: 93%
“…This is based on the observation that the earliest 13-cis BR-K state minus BR dark state FTIR difference spectrum of bacteriorhodopsin with positive bands at 1194 and 1187 cm Ϫ1 and negative bands at 1216, 1202, and 1169 cm Ϫ1 (29,30) is in the fingerprint region similar to the ChR2 difference spectra recorded at 80K. Thus, we conclude that the photoconversion of dark-adapted channelrhodopsin to the 80 K intermediate is triggered by an all-trans to 13-cis isomerization of the retinal.…”
Section: Discussionmentioning
confidence: 99%